PENERAPAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS V DI SD N 095135 SIPOLHA HORISON - Simarmata, Radode Kristianto (Unversitas Katolik Santo Thomas, 2021)
Learning media can be found anywhere. Media has become apart of our lifes in our daily life. Now a days peoples are easier get an information and an enlightenment because of the learning media.The aims of the study is to find out the speaking skill learning effect of students of grade V Primary Civil School 095135 Sipolha Horison,Pamatangsidamanik District, Simalungun Regency in learning English language before using Audio Visual Media. And to find out the Speaking skill effect of students of grade V Primary Civil School 095135 Sipolha Horison, Pamatangsidamanik District, Simalungun Regency after using an Audio Visual Media. From the research result and from the discussion taken by the author , we ot some conclusion : After adopting Audio Visual media, we know that students of grade V Primary Civil School 095135 sipolha Horison,Pamatangsidamanik District, Simalungun Regency are easier to understand the materials or an information which is delivered by the teacher. It means that the aim of the learning can be succeded effectifelly for the subject English language on Muatan lokal subject on students of grade V Primary Civil School 095135 Sipolha Horison,Pamatangsidamanik, District, Simalungun Regency.After developing English Language using an Audio Visual,proves that using an audio visual are more effectively than before taking the develope one.